A Study of Passenger Amenities in Indian Railways with Reference to Vijayawada Division - Prasad, V. Vijay Durga (Indian Journal of Marketing, 2005)
In the service industry where situations as to a promise is sold it is very difficult to assess situations as to where and when these promises fail. Building credibility takes time and requires strategic planning. This makes it clear that it is a difficult proposition to sell these services. Indian Railways always worked on the premise that there is no competition for their services. At times, they felt that there is no need for marketing their services since the demand is much higher than the capacity. But Indian Railways are competing with other modes of transport for both passenger traffic as well as freight. Criss-crossing the country over 63,140 kilometers route having more than 47,147 crores as capital-at-charge and the total investment in the railway system is 70,117 crores and a large workforce of about 15.10 million employees, Indian Railways is second largest railroad system in the world under unitary management. Efficient management of this gigantic infrastructure plays a vital role in the economic, individual and social progress of our country. Indian Railways carried 5093 million passengers and 492.50 million tonnes of freight traffic. All the figures given in this paragraph pertain to year 2001-02. As far as marketing of railway services is concerned, provision of passenger amenities to passengers and rail users is an important element. Providing maximum comfort and amenities to the traveling public is important because of the dwindling market share. The Indian Railways need to have a competitive advantage and customer care in a service industry in one such axiomatic tool. Passengers expect value for money and more so when Railway transportation is an intangible product being an "experience" as service. Providing best passenger amenities should be an end in itself - as a philosophy of the organization.